2013
DOI: 10.1007/s10484-013-9221-x
|View full text |Cite
|
Sign up to set email alerts
|

Focal Electrical Stimulation as an Effective Sham Control for Active rTMS and Biofeedback Treatments

Abstract: A valid sham control is important for determining the efficacy and effectiveness of repetitive transcranial magnetic stimulation (rTMS) as an experimental and clinical tool. Given the manner in which rTMS is applied, separately or in combination with self-regulatory approaches, and its intended impact on brain states, a valid sham control of this type may well serve as a meaningful control for biofeedback studies, where efforts to develop a credible control have often been less than ideal. This study examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…When performing research on non-pharmacological interventions, challenges related to randomization procedures and the use of blinding arise, and randomized controlled trials are not always feasible. 1 , 6 , 22 , 26 , 29 , 40 , 43 Despite the expense of new technologies, rigorously controlled trial designs assessing basic efficacy have not been required for SCS device approvals after the advent of clinical trial registries. Spinal cord stimulation trial designs providing an appropriate double-blind control are problematic because the induction of paresthesias in the area of pain is part of the therapeutic assessment, but the absence of masking can lead to several types of bias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When performing research on non-pharmacological interventions, challenges related to randomization procedures and the use of blinding arise, and randomized controlled trials are not always feasible. 1 , 6 , 22 , 26 , 29 , 40 , 43 Despite the expense of new technologies, rigorously controlled trial designs assessing basic efficacy have not been required for SCS device approvals after the advent of clinical trial registries. Spinal cord stimulation trial designs providing an appropriate double-blind control are problematic because the induction of paresthesias in the area of pain is part of the therapeutic assessment, but the absence of masking can lead to several types of bias.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 14 Device studies of rTMS and tDCS can be more rigorously controlled because the devices are noninvasively applied to the skull, and masking noises, in combination with mimicking the cutaneous sensation and muscular discomfort caused by these types of devices, can effectively blind the wearer to whether or not the device has been turned on. 1 , 40 , 43 Full double-blinding may be possible if all assessments are made by an independent person not involved in operating the device.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The critical question thus is whether blinding success can be achieved under these optimal conditions. Several very similar sham TMS setups have been developed over the years and their perceptual effects and blinding success have been evaluated ( Rossi et al, 2007 ; Arana et al, 2008 ; Borckardt et al, 2008 ; Mennemeier et al, 2009 ; Sheffer et al, 2013 ). The general finding of these studies is that electrical stimulation of the skin results in somato-sensory effects that are very similar to active TMS if the stimulation intensity is individually calibrated ( Arana et al, 2008 ; Borckardt et al, 2008 ; Mennemeier et al, 2009 ).…”
Section: The Placebo Effects Of Tmsmentioning
confidence: 99%
“…Studies supporting the CNDS theory include those demonstrating that a) separate neural systems are activated when choosing SSRs versus LLRs (McClure et al, 2007; McClure et al, 2004; Tanaka et al, 2004), b) transcranial magnetic stimulation of brain structures responsible for executive-system behavior affects delay discounting (Essex, Clinton, Wonderley, & Zald, 2012; Figner et al, 2010; Sheffer et al, 2013), c) steep discounting and executive dysfunction are independently correlated with many of the same maladaptive behaviors (e.g., Gunstad et al, 2007; Kubler, Murphy, & Garavan, 2005; Petry & Casarella, 1999; Roca et al, 2008; Weller et al, 2008), d) taxing the executive system (i.e., increasing working memory load) increases delay discounting (Hinson, Jameson, & Whitney, 2003; but see Franco-Watkins, Pashler, & Rickard, 2003 for an alternative interpretation), e) poor working-memory ability is correlated with steep delay discounting in humans (Shamosh et al, 2008) and in rats (Renda, Stein, & Madden, 2014; but see Dellu-Hagedorn, 2006), f) overlap analyses of neuroimaging studies that separately assessed working memory and delay discounting revealed large activity clusters in the left lateral prefrontal cortex that were unique to these two processes (Wesley & Bickel, 2013), and g) one study has demonstrated decreased delay discounting following working-memory training (WMT) in human stimulant-dependent individuals (Bickel, Yi, Landes, Hill, & Baxter, 2011). In the latter study, participants were randomly assigned to either a WMT group or a sham-training group.…”
mentioning
confidence: 99%